The Nexus between Government Expenditure and Economic Growth: Empirical Evidence from Nepal - Paudel, Shantosh; Khanal, Santosh (Kalika Journal of Multidisciplinary Research, 2024)
The fundamental objective of every government and society in a welfare state is aimed at economic growth and development. Gross Domestic Product (GDP) growth is a consistent measure of economic growth that directly affects a nation's standard of living and overall well- being. This study examines the nexus between government spending and economic in Nepal using time series data using the ARDL model from 1991 to 2022. For the purpose, the study tests the relationship between GDP growth rate as a dependent variable and capital expenditures, recurrent expenditures, government expenditure on health, and inflation rate as four independent variables . The results of the study exhibits that, there exists a direct and consistent link between government expenditure on health and the increase of the Gross Domestic Product (GDP) in the long run. And in the Short-term capital spending has a dynamic effect that eventually influences the long-term growth of Nepal's GDP. The association between recurrent expenditure and inflation with GDP growth is negative, whereas the relationship between capital expenditure and GDP growth is positive. This study suggests that further investigation should explore additional variables and indicators in order to achieve a more comprehensive knowledge of the effect of government spending on economic growth.